The life and music of Elizabeth Maconchy - Siegel, Erica (Musicologist) (The Boydell Press, 2023)
"The first full-length biographical study of Elizabeth Maconchy (1907-1994). The British-born Irish composer (Dame) Elizabeth Maconchy (1907-1994) is best known today for her cycle of thirteen string quartets, composed over five decades. And yet, her oeuvre ranges from large scale choral works, to ballets, operas, and symphonic scores. Having studied with Charles Wood and Ralph Vaughan Williams at the Royal College of Music, many of her compositions also garnered accolades from peers and established musical figures such as Gustav Holst, Donald Francis Tovey, and Henry Wood, among others. With access to a wealth of documentation previously unavailable, this book explores Maconchy's life and music within a greater consideration of the social and political context of the world in which she lived. While the influence of Bartók has been well documented, this book reveals the equally potent influence of Vaughan Williams on Maconchy's musical idiom. This book also discusses Maconchy's foray into administration and her advocacy of young composers through her work as the first woman to be elected Chairman of the Composers'Guild of Great Britain in 1959 and President of the Society for the Promotion of New Music following the death of Benjamin Britten in 1976. It will be required reading for those interested in the lives of women composers, twentieth-century British music, and musical modernism"--